Values and ethics in coaching - Iordanou, Ioanna; Hawley, Rachel; Iordanou, Christiana (SAGE Publications Ltd, 2017)
The first complete guide to exploring values and ethics in coaching, this book will guide you through the responsibilities of coaching practice, and help you recognize and reconcile common ethical dilemmas and choices. Part I explores the theory and research underpinning ethical coaching practice, and invites you to examine own personal and professional values. Part II delves into the key ethical considerations in the coaching relationship, including contracting, confidentiality and understanding boundaries. It explores each issue in depth, and offers implications and suggestions for practice. Part III examines individual professional contexts, including coaching in business, sports and healthcare with real life examples and reflections from practicing coaches. This book is vital reading for trainee and practitioner coaches, and those looking to introduce ethical coaching practice into a professional setting.